2016
DOI: 10.1136/bcr-2016-214724
|View full text |Cite
|
Sign up to set email alerts
|

PHACE syndrome with lip haemangioma, microphthalmos and persistent fetal vasculature

Abstract: An 11-month-old baby girl presented with white reflex in her left eye. On examination, there was a 6.5×5 mm(2)haemangioma present over her face involving on her lower lip. Systemic examinations were within normal limits. The left eye was small, with an axial length of 16.08 mm and had a cataract. Ultrasonography of the left eye was suggestive of the presence of a vascular stalk, persistent hyperplasia of a primary vitreous, or persistent fetal vasculature with vitreous haemorrhage. On MRI, the left eye was sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(5 reference statements)
1
1
0
Order By: Relevance
“…Even though ocular abnormalities are part of PHACES syndrome, Samuelov et al [5] reported that most ocular complications observed in their cohort of 30 patients over 15 years, were secondary to the presence of the large periocular hemangioma itself and were not specific to PHACE(S) syndrome. Nayak et al [10] reported a case similar to ours, an 11-month-old female presented with facial IFH involving the lower lid only, with PFV, VH, and congenital cataract with microphthalmia. She had no associated systemic anomalies.…”
Section: Discussionsupporting
confidence: 76%
“…Even though ocular abnormalities are part of PHACES syndrome, Samuelov et al [5] reported that most ocular complications observed in their cohort of 30 patients over 15 years, were secondary to the presence of the large periocular hemangioma itself and were not specific to PHACE(S) syndrome. Nayak et al [10] reported a case similar to ours, an 11-month-old female presented with facial IFH involving the lower lid only, with PFV, VH, and congenital cataract with microphthalmia. She had no associated systemic anomalies.…”
Section: Discussionsupporting
confidence: 76%
“…Despite its rarity, the presence of lip hemangiomas seems to be associated with a high risk of recurrent late growth hemangiomas after the end of therapy and with a high risk of recurrent ulceration [ 26 ]. Ulcerated upper lip hemangiomas are frequently associated with eyelid ulcerated hemangiomas [ 27 ] or microphthalmia in PHACE syndrome [ 28 ]. Our case presented upper and lower lip ulcerated hemangiomas that were not associated with other facial ulcerated hemangiomas.…”
Section: Discussionmentioning
confidence: 99%